Dry thermal oxidation of GaN with SEM, AFM and XPS characterization - Wei, Daming; Edgar, James H.; Meyer, H.M. (My University, 2011)
The oxidation of group three nitride semiconductors is an important aspect in the fabrication of high power transistors with insulated gates. Gallium nitride (GaN) and its alloys (AlGaN) have electrical properties that are superior to silicon, thus resulting in better performance (greater efficiency, higher power, and higher frequency) in many electronic devices such as high electron mobility transistors (HEMT) and metal oxide semiconductor field effect transistors (MOSFET). Such devices will be greatly enhanced by adding a high quality electrically insulating layer, and this may be prepared by thermal oxidation. Thus, the dry thermal oxidation of polycrystalline GaN powder and GaN epitaxial layers was studied, over the oxidation temperatures from 800 °C to 1000 °C for up to 6 hours. The physical and chemical properties of the oxides were characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM) and x-ray photoelectron spectroscopy (XPS) respectively. An amorphous oxide layer formed at 800°C, but polycrystalline Ga2O3 was detected at a temperature over 850°C. As the oxidation temperature was increased, the oxide surface becomes rougher. The thickness of the oxide forming on the GaN epilayer was calculated according to a depth profile plotted with XPS data. A very thin oxide layer was formed from 800°C to 850°C over 6-hour oxidation. The oxidation rate was controlled by an interfacial-controlled reaction mechanism at low temperatures (~800 °C) and diffusion controlled at high temperatures (1000 °C).
Keywords: Dry thermal oxidation; GaN; Atomic force microscopy (AFM); Scanning electron microscopy (SEM); X-ray photoelectron spectroscopy (XPS)